Pengajaran Literasi dan Penilaian Portofolio dalam Konteks Pembelajaran Menulis di SD - Muhana Gipayana (Universitas Negeri Malang, 2016)
This classroom action research was aimed at maximizing the quality of teaching writing by adopting the concept of literacy learning and portfolio assessment. The subjects were 5th-grade students of SDN Pisang Candi I, II, and III Kodya Malang. The design implemented was the three-cycle model by Kemmis and McTaggart (1988). The results indicated that the quality of teaching writing improved. The students motivation could be enhanced, their reading and writing activities were observable, and their writing skill was well developed.